AutoCAD 2019 : beginning and intermediate - Hamad, Munir M. (Mercury Learning and Information, 2019)
Includes over 100 exercises or mini-workshops that complete small projects from concept through actual plotting, this comprehensive book on AutoCAD 2019 2D drafting uses both metric and imperial units to illustrate the myriad drawing and editing tools for this popular application. --